Predictors of HIV Knowledge, Perceived Stigma and Risk among Transport Workers in Mbarara City, Southwestern Uganda - Betunga, Benjamin; Nuwabine, Lilian; Katushabe, Eve; Among ,Grace; Asiimwe, John Baptist (The East African Health Research Journal, 2024)
The human immunodeficiency virus (HIV) prevalence among transport workers in sub-Saharan Africa remains high, estimated at as high as 9.9% in western Uganda compared with the national prevalence of 5.4%. The prevalence of HIV among transport workers has been partly attributed to the level of knowledge regarding HIV prevention, perceived HIV risk, and stigma. Accordingly, these have been linked to high-risk HIV transmission behaviours that increase the chances of acquiring HIV among adults. Therefore, this study investigated the predictors of HIV knowledge, perceived HIV risk, and stigma among transport workers in Mbarara city in southwestern Uganda.